Determination of optimal intensity measure for probabilistic seismic demand analysis of intake towers. (December 2021) - Haghgou, Hossein; Alembagheri, Mohammad; Bigdeli, Ali
Abstract: Establishing a probabilistic seismic demand model (PSDM), which illustrates the relationship between ground motion intensity measures (IMs) and engineering demand parameters (EDPs), is a critical step in the performance-based earthquake engineering (PBEE) framework. This model expresses the probability of a system experiencing a specific level of demand for a certain IM level. The optimal IM selection for intake towers taking soil-structure-water interaction into account has not been studied previously, and this research uses the Wimbleball intake tower as a case study. First, IMs and EDPs are chosen and classified based on their specifications. The optimal probabilistic seismic demand model is then determined by evaluating the IM-EDP charts generated for 150 ground motion records on a logarithmic scale using goodness of fit, practicality, efficiency, proficiency, and sufficiency criteria. By determining the optimal IM, it is possible to identify which IM has the greatest impact on structural response and better reveals the general trends of damage and failure. The Cordova intensity is determined to be the best option for the intake towers. Finally, seismic fragility curves are displayed, which represent the probability of EDP exceedance in terms of the IM parameter and can be used to assess initial damage to the structure.